Adapting to a new normal Colombia edition: Stories of livestock keepers navigating climate challenges - Vanegas, Carlos José; Moreno, J. (International Livestock Research Institute, 2025)
In this booklet you’ll read about farming families in Colombia’s Caquetá department who are leading the way in reshaping livestock production in the face of climate change. In Colombia, the Pioneer Positive Deviance approach was used to identify and learn from livestock keepers who, despite facing the same challenges as their neighbours, have developed unique and effective strategies for thriving in a changing climate. These pioneers are improving their herds, protecting forests and water sources, diversifying their farms, and sharing their knowledge with others.